Women Sentiments and Urdu Novel - Ahmed, Waqar; Iqbal, Sajid; Shehzad, Azmat (sourcecoder, 2022)
Urdu Fiction, from abinitio till date, construction womanhod as natural phenomenon embedden in different feeling and thoughts of social life. She is unfolded as social being whose emotional life is a byproduct of social odds. Her psyche, indifferent writing shrinks in culture limits--marginalisingaborignal--and expands in modern settings--advocating modernity. Abusive female character is ingrained in social conditions making a point to inferior culture of scheduled castes. The novels under discussion present a very interesting situation where corrective attitude of Molvi Nazeer Ahmad place woman in postmodern world of today reflecting all qualities of postmodern world.